Prevalence and Correlates of Depressive Symptoms Among International Students: Implications for University Support Offices - Shadowen, Noel L; Williamson, Ariel A; Guerra, Nancy G; Ammigan, Ravichandran; Drexler, Matthew L (Journal of International Students, 2019)
International students often experience significant challenges and difficulties adjusting to their new campus and university environment abroad. As a result, understanding the unique needs of these students has become an important priority for many university administrators and mental health professionals amid growing health concerns faced by members of this community. This study examines the prevalence and correlates of depressive symptoms in a sample of international students enrolled in a mid-size U.S. university. A hierarchical multiple regression model revealed that poor English fluency, increased acculturative stress, and perceived discrimination were associated with higher levels of depressive symptoms, whereas increased social support was associated with lower levels of depressive symptoms. Implications for university administration and support services are discussed.